KINETIC STUDIES USING SEMI-EMPIRICAL SELF- CONSISTENT FIELD (SCF) MOLECULAR ORBITAL (MO) METHOD: PARTI. A MODIFIED NEGLECT OF DIATOMIC OVERLAP (MNDO) STUDY OF THE PYROLYSIS OF ETHYL VINYL ETHER (Journal of Sciences, Islamic Republic of Iran)
Using a computer code called MOPAC, an acronym for a general Molecular Orbital Package (Quantum Chemistry Programme Exchange (QCPE) Programme No. 455), the geometries and heats of formation of the reactant, the products and the trdnsition state were computed by the MNDO semi- empiricalself consistent field (SCF) method for the pyrolysis of ethyl vinyl ether. ((Force))calculation on the reactant and the transition state also gave the enthalpies and entropies at various selected temperatures. In the temperature range of the experimental pyrolytic study, the above calculations yielded the Arrhenius parameters of the reaction in excellent agreement with reported experimental results. This is significant in that it supplements the number of instances [I, 2,3(a)- (g)], not exhaustively enumerated here, in which a semi- empirical SCF method has been successfully used to study the reaction mechanisms of many- atom molecules